Reliability and Validity Testing of the FAMCARE-2 Scale: Thai Translation - Ladarat Ooraikul; Virapun Wirojratana; Rochana Phuackchantuck; Payuree Chompukeaw; Chiraporn Khaisuwan (Elsevier, 2020)
Objective: Measuring the satisfaction of family caregivers regarding the palliative care provided to their family members is very important for quality improvement in the palliative care system. The aim of this study was to test the psychometric properties (i.e., reliability and validity) of the FAMCARE-2 Scale: Thai Translation for measuring family caregiver satisfaction. Methods: A forward-backward translation process was utilized to produce the 17-item FAMCARE-2 Scale: Thai Translation. The questionnaire and the demographic data form were hand-delivered to the primary family caregivers of 66 palliative care patients of the inpatient wards at Maharaj Nakorn Chiang Mai Hospital, Faculty of Medicine, Chiang Mai University, on the patient discharge date. Internal consistency reliability testing of the FAMCARE-2 Scale: Thai Translation was assessed by calculating the Cronbach's alpha coefficient. Factor analysis was used to test construct validity. Results: The FAMCARE-2 Scale: Thai Translation showed a high level of internal consistency (Cronbach's alpha coefficient of 0.94) and an item-to-total correlation coefficient of 0.13-0.77. Factor analysis of FAMCARE-2 revealed a four-factor structure: management of physical symptoms and comfort, patient care and sharing information, symptoms and side effects, and family and patient support. Conclusions: The FAMCARE-2 Scale: Thai Translation was found to be a valid psychometric tool for measuring family caregiver satisfaction within the Thai context of palliative care.